School Segregation Policy and Its Educational Ramifications for Internal Migrant Children in Urban China (Asian Journal of Social Science Studies, 2017)
This paper reviews the current state of education for internal migrant children in urban China, with the aim of teasing out its ramifications for pedagogic equity expressed as performance outcomes. In recent years migrant children have been segregated predominantly in urban migrant schools, whereas students with a higher socioeconomic status may have access to integrated public schools populated mostly by urban children. This paper analyses publicly accessible policy papers and relevant scholarly literature to provide a contextualised interpretation of school segregation, with an aim to advance societal recognition of and responsibility for the inequities associated with the education of migrant children in China. Our intention is to tease out and make more transparent than has to date happened the implications of these disparities and inequities. It is to be hoped that this information will encourage policy makers to acknowledge that the amelioration of inequities in performance depends on reforming the current segregation procedures and administrative protocols which fail to maximise the access to equal educational opportunities to which Chinese migrant students should be entitled.